(untitled) (Biological Sciences - PJSIR, 1995)
The major and trace elements in millet and soil samples of three different experimental farms on the beaches of High Dam Lake (Kalabsha, Gerf Hussein and Allaqi) at 10,30,60 ern depths were determined using atomic absorption spectrophotometer (AAS). ion selective electrode (ISE) and titrimetric techniques. The results indicated that in Kalabsha, the soil samples at 30 cm depth exhibited high concentrations of Ca, Co, Cr, Fe, K, Mg, Na, Ni, Pb, Sr and Zn. High concentration of Ca. CI, K, Mg, and Na were detected at 10 ern depth in soil of Allaqi. Higher concentration of elements were found in millet planted in Allaqi area than that planted in the other two areas. Good correlation coefficeint values were found between the elements in millet, soil samples and millet/soil ratio.